An outbreak of pleural mesothelioma and chronic fibrosing pleurisy in the village of Karain/Urgüp in Anatolia. - Baris, Y I (1978)
The 575 inhabitants of the remote Anatolian village of Karain suffered 11 deaths from pleural mesothelioma in 1975/76 and there were five cases of fibrosing pleurisy. In the previous five years there had been 25 cases of mesothelioma. Calcified pleural plaques were common on survey radiography. Asbestos does not occur in the local soil or rock, nor is it handled in the village, but a few fibres were found in the water. Fibres were also found in the pleural tissue of two of five cases examined. Inhabitants of the neighbouring villages are free of mesothelioma.